Coping with circumstance : development, and application to niche software development firms, of an integrative process model of adaptation - Coleman, John Dominic (Trinity College (Dublin, Ireland). Trinity Business School, 2006)
The research described in this thesis uses process theory to examine the phenomenon of adaptation in niche software development firms. This examination is undertaken by initially constructing a model of adaptation that conforms to established criteria for process theory. This model is then applied to instances of adaptation, identified in case studies of four Irish indigenous software development firms. The research integrates key concepts from important streams of theory on organisational adaptation into a theoretically cohesive model that can be used to examine the phenomenon of adaptation. The purpose of the research is 1) to verify that a multi-stage process model of adaptation can be built that meets given criteria, 2) to test the model in real-life settings and, on the basis of those tests, 3) to uncover patterns of adaptation in niche software development firms.
Keywords: Business Studies, Ph.D.; Ph.D. Trinity College Dublin